2020
DOI: 10.3390/w12092456
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Integrated Nitrate Reduction across the Unsaturated Zone and the Groundwater Body in Germany

Abstract: Nitrate pollution in groundwater and its mitigation strategies is currently a topic of controversial debate in Germany, and the demand for harmonised approaches for the implementation of regulations is increasing. Important factors that need to be considered when planning mitigation measures are the nitrogen inputs into water bodies and the natural nitrate reduction capacity. The present study introduces a nationwide, harmonised and simplified approach for estimating nitrate reduction as an integral quantity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…For example, recent observations and modeling work in Germany found 95% of the N surplus may be denitrified along groundwater pathways before even reaching surface water, while other catchments showed little to any capacity to remove N surplus through subsurface pathways. This database can thus be used for management and further research purposes to explore relationships between surplus and stream export and identify factors that modify this relationship ( Knoll et al 2020 ). Second, ranking subbasins only by mass of N and P would likely lead to larger basins being ranked higher than smaller basins largely due to the difference in area rather than the intensity of fluxes or surpluses.…”
Section: Methodsmentioning
confidence: 99%
“…For example, recent observations and modeling work in Germany found 95% of the N surplus may be denitrified along groundwater pathways before even reaching surface water, while other catchments showed little to any capacity to remove N surplus through subsurface pathways. This database can thus be used for management and further research purposes to explore relationships between surplus and stream export and identify factors that modify this relationship ( Knoll et al 2020 ). Second, ranking subbasins only by mass of N and P would likely lead to larger basins being ranked higher than smaller basins largely due to the difference in area rather than the intensity of fluxes or surpluses.…”
Section: Methodsmentioning
confidence: 99%
“…Although in certain conditions the groundwater environment enables some decrease of nitrates concentration (e.g. Højberg et al, 2017;Knoll et al, 2020a), the capacity of this mechanism is exhaustible (Knoll, et al, 2020b;Kunkel et al, 2017). Therefore, the dilution of groundwater with less polluted percolation water often remains the most available way to reduce an excessive nitrate concentration in groundwater (Mas-Pla, Menció, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This is only possible if the groundwater managers have decision tools to spatially predict the nitrate concentration. On one hand, there is a lot of research going on in the field of modeling nitrate in groundwater bodies, mainly on the basis of geostatistical methods such as kriging (Wriedt et al, 2019), numerical models (Nguyen and Dietrich, 2018), and tree-based models such as the random forest (Breiman, 2001;Knoll et al, 2020;Mandal et al, 2023;Sarkar et al, 2023) and gradient boost regression trees (Friedman, 2002). Breiman (2001) showed that the random forest model gives an opportunity for support to water managers and authorities in developing strategies for measures to reduce nitrate inputs into the groundwater.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Mendes et al (2016), Ouedraogo et al (2018) and Sarkar et al (2022) applied random forest regression to model groundwater nitrate concentration. Boosted regression trees have been successfully used to fit machine learning models for predicting groundwater nitrate (Ransom et al, 2017(Ransom et al, , 2022Knoll et al, 2020). Although attempts have been made to incorporate information about an observation's surroundings into the predictor variables of a random forest model, this information still lacks a spatial reference.…”
Section: Introductionmentioning
confidence: 99%